Governing Islam in Plural Societies: Religious Freedom, State Neutrality and Traditional Heritage. Issue 1 (2nd January 2017) - Elbasani, Arolda
Abstract: Post-Communist openings constituted the ideal foci for reimagining the relationship between the state and religion. Specifically, new opportunities were created to balance between rules of inclusion and exclusion regarding contending alternatives of a 'good life'. In line with their new democratic aspirations, all Balkan countries have gradually reshuffled their religious policies, formalized religious freedoms, and institutionalized a more equal playing field for their respective religious communities. Realizing an all-inclusive and equal-opportunity structure for all religious denominations, however, proved neither smooth nor automatic, especially when it came to the inclusion of the historically marginalized Muslim populations. The evolving institutional choices to incorporate these communities vacillated between the democratic urge for religious freedoms and equality, on the one hand, and the role of founding traditions and heritage of majority privileges, on the other. This article outlines the institutional compromises to accommodating Islam across plural polities which feature an unusual mix of denominations—Muslim, Christian Orthodox, Roman Catholics as well as atheist and agnostic groups—in the post-Communist Balkans.